Antimicrobial use and incidence of multidrug-resistant pseudomonas aeruginosa in a teaching hospital: An ecological approach - das Neves, Mariana Tresoldi [UNESP]; de Lorenzo, Mariana Eliza Pinto [UNESP]; Almeida, Ricardo Augusto Monteiro Barros [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (FapUNIFESP (SciELO), 2010)
Introduction: Multidrug-resistant Pseudomonas aeruginosa is a major threat in healthcare settings. The use of antimicrobials can influence the incidence of resistant strains by direct and indirect mechanisms. The latter can be addressed by ecological studies. Methods: Our group attempted to analyze the relation between the use of antipseudomonal drugs and the incidence of MDR-PA among 18 units from a 400-bed teaching hospital. The study had a retrospective, ecological design, comprising data from 2004 and 2005. Data on the use of four antimicrobials (amikacin, ciprofloxacin, ceftazidime and imipenem) were tested for correlation with the incidence of MDR-PA (defined as isolates resistant to the four antimicrobials of interest) in clinical cultures. Univariate and multivariate linear regression analyses were performed. Results: Significant correlations were determined between use and resistance for all antimicrobials in the univariate analysis: amikacin (standardized correlation coefficient = 0.73, p = 0.001); ciprofloxacin (0.71, p = 0.001); ceftazidime (0.61, p = 0.007) and imipenem (0.87, p < 0.001). In multivariate analysis, only imipenem (0.67, p = 0.01) was independently related to the incidence of multidrug-resistant strains. Conclusions: These findings share similarities with those reported in individual-based observational studies, with possible implications for infection control.
Uso de antimicrobianos e incidência de pseudomonas aeruginosa multidroga-resistente em um hospital de ensino: Uma abordagem ecológica
Keywords: Antimicrobial resistance; Ecological study; Pseudomonas aeruginosa